FRI0229 Evaluation of Patient Acceptable Symptom State in Patients with Axial Spondylarthritis; Similar Thresholds for Radiographic and Non-Radiographic Subgroups. (9th June 2015) - Cetin, P.; Sen, G.; Kenar, G.; Yarkan, H.; Zengin, B.; Sari, I.; Birlik, M.; Onen, F.; Akkoc, N.
Abstract : Background: The Patient Acceptable Symptom State (PASS), a single-question outcome, has been defined as an absolute level of patient well-being. A few studies have assessed PASS in patients with ankylosing spondylitis (AS), but it is not known whether the results of those studies apply also to the group of non-radiographic (nr) axial spondylarthritis (axSpA) Objectives: To estimate the PASS values for disease activity and several patient reported outcomes both in the whole group of axSpA and in the two subgroups of AxSpA. Methods: This single-center cross-sectional analysis included patients fulfilling the ASAS criteria for axSpA, who have been registered in our local database. All patients responded to the global yes/no question for PASS. A variety of other outcome measures in regard with global scales, disease activity, functional status, health status and quality of life were collected at the same time. The thresholds at which patients rated themselves in PASS for disease activity (BASDAI and ASDAS) and for each of the assessed patient self-reported outcome measures were estimated using the 75th centile (25th centile for SF 36)estimation and receiver operating characteristic (ROC) analyses in the whole group, as well as in each subgroup of axSpA. Contributors which can affect PASS were evaluated with logistic regression analysis. Results: The analysis was based on 356 axSpA patients (261 AS, 95 nr-axSpA) with a mean age of 42.2±12.0 years and mean disease duration of 14.7±10.8 years. Of the patients with axSpA, 271 (%76.1) considered themselves in PASS (76.6% in AS, 74.7% in nr-axSpA). PASS thresholds for disease activity and all other assessed outcome measures were shown in table and there were not significant difference between AS and nr-axSpA group. PASS cut-off points for BASDAI, BASFI and HAQ identified by the 75th percentile method were slightly higher than those determined by the ROC analysis, but similar for the rest of the outcome measures. The patients with an acceptable status had significantly lower mean disease activity scores and good results with the all outcome measures. PASS had no relationship with age, sex, disease duration and education (years) in logistic regression analysis. Of the axSpA patients with BASDAI (≥4), 61.4% and those with ASDAS (>3.5), 50% rated themselves in PASS, whereas 5.5% of the patients with a BASDAI score <2, and 4.5% of those with ASDAS <1.2 were not in PASS. Conclusions: PASS thresholds for disease activity and outcome measures were similar to the figures previously reported in some studies with no apparent difference between patients with AS and nr-axSpA. However, more than half the Turkish axSpA patients considered themselves in PASS, which needs to be evaluated in further studies. Disclosure of Interest: None declared